THE POSITION OF VICTIMS OF SEXUAL CRIMES IN RNM (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2025)
This research paper examines the legal status, rights, and procedural position of victims of sexual crimes within the legal system of the Republic of North Macedonia. It analyzes the relevant provisions of the Criminal Code and the Law on Criminal Procedure, alongside international conventions and human rights standards ratified by North Macedonia. Particular emphasis is placed on the harmonization of domestic legislation with the Istanbul Convention. The study provides an in-depth analysis of procedures related to the reporting and collection of evidence in sexual crime cases, including the use of Rape Kits. It further explores the extent to which the domestic legal framework ensures effective protection and support for victims, with a focus on measures aimed at preventing re-victimization and re-traumatization during criminal proceedings. Empirical data obtained from the Ministry of Internal Affairs, covering the period 2020–2025, is used to illustrate trends in the reporting of sexual offenses. The findings reveal significant shortcomings in the current legal framework that hinder the adequate treatment of victims and contribute to their re-victimization. The paper concludes with concrete recommendations for legislative and procedural reforms, aimed at enhancing both the substantive and procedural rights of victims of sexual crimes and improving the overall legal response to these serious offenses in North Macedonia.Keywords: Istanbul Convention, victims, sexual crimes, rights, law